Does the Fisher hypothesis hold for the G7? Evidence from the panel cointegration test - Ozcan, Burcu; Ari, Ayse (Routledge Journals, Taylor & Francis Ltd, 2015)
The aim of this study is to investigate the validity of the Fisher hypothesis by assessing the relationship between the nominal interest rate and the inflation rate. To this end, we analyse the G7 countries over the period January 2000 to November 2012 by employing the panel unit root and panel cointegration tests. The analysis reveals that the adjustment in nominal interest rates to changes in inflation is significantly lower than unity, which implies the existence of a partial Fisher effect.
Keywords: Fisher hypothesis; monetary policy; inflation rate; interest rate; panel unit root test; panel cointegration test